The Urgency of Presidential Institution Regulations in Strengthening the Presidential Government System - Widayati, Widayati; Haji Mohiddin, Mas Nooraini binti; Herawati, Ratna; Winanto, Winanto (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The existence and authority of the executive, legislative and judicial institutions are regulated in the 1945 Constitution of the Republic of Indonesia, then regulated in more detail in the law, except for the President. There is no law on presidential institutions yet, so there is concern that the President will exceed or abuse his authority in carrying out his duties. This research discusses the importance of regulating presidential institutions in strengthening the presidential system. The research approach was normative juridical; examining legal rules or regulations as a building system related to a legal event. The data used were secondary data in the forms of primary and secondary legal materials. Based on the results of the analysis, it is concluded that: 1) the regulation of presidential institutions is only found in the Constitution. There is no description of the position and division of authority between the President and Vice President and other positions in the presidential institution. 2) The position of the Vice President is as assistant to the President, and the Vice President replaces the President when the President dies, resigns, is dismissed, or is unable to carry out his obligations during his term of office. 3) Regulation of presidential institutions in strengthening the presidential government system is very urgent to prevent arbitrary actions by the President and to provide clarity on the authority of positions within the presidential realm so that they can carry out their duties well in supporting the President as head of state and head of government. With clear arrangements, each person has responsibilities, and there will be no overlapping of authority.